Análisis de contenido cuantitativo sobre gestión del conocimiento en instituciones de educación superior latinoamericanas - Huanca Guanca, Juan Carlos; Portal Gallardo, Jaime Anisio (Universidad de Costa Rica, 2023)
The objective of this research was to determine the state of the art of knowledge management in a group of Latin American universities based on an analysis of academic publications according to the criteria of: knowledge management evolution according to generations, use of management models of knowledge and knowledge management in the substantive functions of teaching, research and university extension. The population consisted of 49 academic publications indexed in Google Scholar, published from 2004 to 2021 in 14 Latin American countries and the quantitative approach was used for analysis. The study shows that most of the publications correspond to the second and third generation of knowledge, by identifying the SECI model (Socialization, Externalization, Combination and Internalization) as the most referenced model. The development of their own knowledge management models reaches 41% of the jobs, mainly in Bolivia, Colombia, Mexico, Peru and Venezuela. The results allow us to identify the degree of evolution of the use of knowledge management from the generations of knowledge, the most used knowledge management models and their application around the substantive functions of the university.